Comparison of Orthodontic Treatment Duration Among Extraction Versus Non Extraction Therapies - Kafle, Dashrath; Mishra, Rajeev Kumar; Mahto, Ravi Kumar; Luintel, Sanjeev; Shrestha, Suja; Sangroula, Samikshya (Orthodontic Journal of Nepal, 2019)
Introduction: Orthodontic treatment is usually perceived as a lengthy treatment as average treatment time usually last more than a year and may go up to even five years. So, in orthodontic practice the optimum treatment result with minimal treatment time should be the goal of clinicians. Treatment duration varies based on different clinico-environmental factors. Materials & Method: Total 200 cases were randomly selected from the archives of debonded treatment records from the department of orthodontics, Dhulikhel Hospital, Kathmandu University Teaching Hospital. Out of the 200 records, 103 records were fit for the study based on previously set inclusion and exclusion criteria. The selected cases were divided into three different groups: extraction n= 28 (extraction of 4 premolars), partial extraction= 19, (extraction of 1-3 teeth) and non-extraction n=56. Furthermore, the cases were also divided into Class I, II and III malocclusion patterns. After doing the test of normality, descriptive statistics, independent samples t test and ANOVA test were performed to compare the treatment duration with respect to gender, malocclusion pattern and treatment modalities. Result: Out of the 103 selected cases, maximum number of cases were of Class I(60) followed by Class II(37) and Class III(6). There was no statistical significance on treatment duration among male and female subjects (p= 0.933) as well as among different malocclusion pattern ( p= 0.255). On the contrary, there was statistical difference on treatment duration among non extraction, partial extraction and extraction groups ( p=0.0004). The average treatment duration for non extraction, partial extraction and extraction group were 22, 28 and 29 months respectively. Conclusion: Orthodontic treatment duration is shorter for therapies done by non extraction than extraction. The average treatment duration for non extraction and extraction therapy is 22 and 29 months respectively. The treatment duration is not affected by gender and type of malocclusion.